2003
DOI: 10.1002/humu.9165
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin analysis by DHPLC in French POAG patients: Increased prevalence of Q368X mutation

Abstract: Primary open-angle glaucoma (POAG) is a prevalent optic neuropathy with complex genetics. A small number of patients carry a mutation in the coding region of the myocilin (MYOC) gene. The nature and the frequency of these mutations, however, vary substantially, notably with the age at onset and the ethnic origin of the patients. Here, we showed that denaturing high performance liquid chromatography (DHPLC) is an appropriate method for screening carriers of MYOC mutations. We have applied the method to a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
(55 reference statements)
1
18
1
5
Order By: Relevance
“…Single Nucleotide Polymorphism OPTN Variant Defective in Htt Binding-The OPTN gene was recently reported to possess both causal and risk-associated alleles for open angled glaucoma (20,30,31). We found that one missense single nucleotide polymorphism OPTN mutant, OPTN-H486R, demonstrated reduced association with N-Htt Q138 (52 Ϯ 20% of wild-type OPTN binding) but was unimpaired in either FLAG-mGluR1a or N-Htt Q15 binding (Fig.…”
Section: Impaired Mglur Signaling In Striatal Cells Derived From Hdh mentioning
confidence: 70%
See 1 more Smart Citation
“…Single Nucleotide Polymorphism OPTN Variant Defective in Htt Binding-The OPTN gene was recently reported to possess both causal and risk-associated alleles for open angled glaucoma (20,30,31). We found that one missense single nucleotide polymorphism OPTN mutant, OPTN-H486R, demonstrated reduced association with N-Htt Q138 (52 Ϯ 20% of wild-type OPTN binding) but was unimpaired in either FLAG-mGluR1a or N-Htt Q15 binding (Fig.…”
Section: Impaired Mglur Signaling In Striatal Cells Derived From Hdh mentioning
confidence: 70%
“…Recent studies have demonstrated that single nucleotide polymorphism OPTN variants are associated with hereditary forms of normal tension glaucoma (20,30,31). Alterations in mGluR signaling are also implicated in contributing to the etiology of glaucoma (37).…”
Section: Discussionmentioning
confidence: 99%
“…22 Probands of PCG families were reported previously. 18 A protocol approved by the Ethics Committee of Necker Medical School and in keeping with European legislation was followed.…”
Section: Patientsmentioning
confidence: 99%
“…The oven temperature and gradient conditions for heteroduplex detection were predicted with WaveMaker software (version 4.1.40) and specified experimentally as described previously. 22 Actual parameters for DHPLC analysis of CYP1B1 amplicons were established in this work and are listed in table 1. PCR products from DNA to be tested were mixed with an equimolar amount of PCR product from a DNA sample known to be unmutated.…”
Section: Cyp1b1 Mutation Searchmentioning
confidence: 99%
“…5,8 Early genetic diagnosis in glaucoma can help prevent irreparable ocular damage if caused by MYOC mutations, where elevation of intraocular pressure (IOP) can be quite pronounced and outcomes can be severe. 9 Prevalence of glaucoma varies among populations, showing values ranging from 1.7% to 2.1% for whites over the age of 40, to 4 times this percentage for populations of African descent. 10 There are ethnogeographic differences in distribution of MYOC mutations.…”
mentioning
confidence: 99%